Building trustful relationships through intrapreneurship in Academic Development - Karen Heard-Lauréote; Carina Buckley (Journal of Learning Development in Higher Education)
Trust between people who develop academics (Academic Developers) and academics is not always straightforward, and where trust does exist, it can often be limited to the individuals involved in the interaction, rather than extending to the wider institutional culture. This lack of trust can be attributed to a variety of factors, one of which is the perception that Academic Developers are merely a management tool focused on performance metrics rather than upholding quality standards. Academic Developers' cognitive authority can also be challenged by institutional and administrative authority, affecting trust between academics and developers. This reflection aims to explore barriers to the development of trust between Academic Developers and academics before proposing changes in practice to bridge the trust gap. The main focus of this reflection is to scale trust beyond individual relationships and promote a culture of trust within the institution. By doing so, we advocate for an approach that works towards building a more trusting environment in HE that fosters collaboration, creativity, and success, given that Academic Developers' role as a ‘broker’ between the institution and colleagues is becoming more prevalent. We argue, however, that efforts to achieve more robustly trustful relationships between Academic Developers and the communities they serve require investment, buy-in and championing by senior executive teams to ensure Academic Developers are themselves appropriately developed to fulfil their potential. As such, we propose a framework for building trust through integrating intrapreneurship in Academic Developer CPD activity.